2011
DOI: 10.1007/s10802-011-9512-8
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Parenting Intervention on Features of Psychopathy in Children

Abstract: This study examined whether Project Support, a parenting intervention shown to reduce child conduct problems, also exerts positive effects on features of psychopathy in children. Participants were 66 families (mothers and children) recruited from domestic violence shelters who participated in a randomized controlled trial evaluating Project Support. Each family included at least one child between the ages of 4 and 9 who was exhibiting clinical levels of conduct problems. Families were randomly assigned to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
76
1
4

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(89 citation statements)
references
References 44 publications
7
76
1
4
Order By: Relevance
“…Harsh or punitive parenting has been significantly associated with increased levels of CU traits and ODD over time, in children with ages ranging from 3 to 10 [21] and 4 to 9 [22]. Similar findings were observed in a high-risk sample of preschoolers age 2 to 3 [8].…”
Section: Parenting Practices As a Risk Factor For Cu Traitssupporting
confidence: 71%
“…Harsh or punitive parenting has been significantly associated with increased levels of CU traits and ODD over time, in children with ages ranging from 3 to 10 [21] and 4 to 9 [22]. Similar findings were observed in a high-risk sample of preschoolers age 2 to 3 [8].…”
Section: Parenting Practices As a Risk Factor For Cu Traitssupporting
confidence: 71%
“…Although sex differences have been noted in the heritability and trajectory of CU traits and psychopathy, 13,39 previous research has not examined potential sex differences in intervention effectiveness on CU traits. [40][41][42] An additional finding of interest was the moderate and positive levels of agreement between CU traits and both dimensional and diagnostic measures of externalizing psychopathology. Findings from the English and Romanian Adoption Study 25 indicated that high levels of CU traits were not significantly associated with CD, leading the authors to speculate that psychopathy exists outside the context of CD and should be diagnosed independently.…”
Section: Discussionmentioning
confidence: 99%
“…Es decir, la capacidad de medir confiablemente los niveles de castigo, la entrega de ganancias materiales, la interacción social positiva entre padres e hijos, la impartición de normas, el uso de ganancias sociales, el establecimiento de límites, el involucramiento positivo entre la diada, la parentalidad positiva, el monitoreo y la supervisión, la inconsistencia en la disciplina, el uso del castigo corporal, la ocurrencia de conductas de oposición y desafío, la disrupción/agresión, la hiperactividad y la inatención, todo ello con la muestra del estudio, lo que permite la validación de los resultados finales. Así, fue posible evaluar el nivel predictivo de las prácticas de crianza, de clasificación negativa (Clark & Frick, 2016, McDonald et al, 2011Morales et al, 2017) sobre la conducta moderadamente problemática reportada por los padres (Hawes et al, 2014).…”
Section: Discusión Y Conclusionesunclassified
“…Morales et al (2017) reportaron un mayor índice de involucramiento positivo e interacción social, como prác-ticas positivas, en el grupo de padres con niños sin problemas de conducta. También señalaron que la agresión infantil parece jugar un papel relevante en la asociación de las prácticas negativas (castigo corporal o inconsistencia en la disciplina) y positivas (interacción social e involucramiento positivos), con los problemas severos de conducta (también revise McDonald et al, 2011).…”
Section: Introductionunclassified